Synthesis and Study of Influence of the Methylene Group Quantity on the Structural Behavior of Polymethylene-Quinazolinethiones. (Journal of Basic and Applied Research in Biomedicine, 2022)
6,7,8,10-Tetrahydropyrrolo[2,1-b]quinazolin-10-thione (4), 6,7,8,9-tetrahydro-11H-pyrido[2,1-b] quinazoline-11-thione (5), and their seven-membered homologue - 6,7,8,9,10,12-hexahydroazepino[2,1-b]quinazolin-12-thione (6) have been synthesized by interaction of corresponding quinazolones (1-3) with phosphorus pentasulfide. First time the comparable X-ray crystal structure analysis of polymethylenequinazolinethiones (4-6) are studied. It was revealed some regularity of the structure of obtained thiones 4-6 by XRD and identified the conformational state cycloalkanoic rings and the reactivity of the methylene protons at C-6.